Antifungal Activity of Eugenol Loaded Electrospun PAN Nanofiber Mats Against Candida Albicans - Semnani, Kourosh; Shams-Ghahfarokhi, Masoomeh; Afrashi, Mehran; Fakhrali, Aref; Semnani, Dariush (Current Drug Delivery, 2018)
Background: Eugenol, as the major phenolic component of clove essential oil due to its desired properties in medical field, was loaded into polyacrylonitrile (PAN) nanofibers with various percentages. Objective: Our main purpose in this study was to determine the in vitro antifungal activity of eugenol loaded on PAN nanofibers against Candida albicans as the most common causative agent for candidiasis. Method: Also, the surface morphology and the mechanical properties of nanofibers were studied by scanning electron microscope (SEM) and a tensile tester, respectively. The average diameters of nanofibers in pure PAN nanofibers were found to be 127 nm. Results: The results showed that the average diameter of nanofibers after increasing the eugenol ratio (from 127 to 179-218 nm) was increased. Drug release profile of the samples was gradual and was completed after 150 hours. Conclusion: According to the results, these nanofiber mats loaded with eugenol can be used for treating cutaneous mucocutaneous candidiasis in high risk patients as a coating on a fabric substrate or temporary wound dressing.
Keywords: electrospinning